Semiotic Analysis of the Cover of the Corruptor Jokes Book, a Collection of Short Stories by Agus Noor - Marzuqi, M. Rifqi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The book of Jokes on Corruption, a collection of short stories, is a book by Agus Noor, which was published in 2017. There are many other short stories that also have the same theme as the main short stories or short stories that have become icons and even become titles in short story collections. In research discussing the cover of a collection of joke short stories for corruptors, book covers are always iconic and also give the first impression on book readers. The icons created by the illustrator are also not arbitrary and have a meaning that makes a book perfect. Like the illustration of a doll that depicts corruptors who are caught, it turns out to be just a doll or the victim of a group of other corruptors. The method used in this research is to use a qualitative descriptive method with Charles Sanders Pierce's semiotic analysis approach, so signs in images can be classified with semiotics such as icons, indexes, and symbols, but in this study the focus is more on icons. The results of the research produce meanings that will be understood by many people who read them.